The impact of an educational software designed about fundamental of nursing skills on nursing students\' learning of practical skills - Marzeieh Khatooni (Majallah-i Bālīnī-i Parastārī va Māmāyī, 2014)
Background and aims: Educational software is a learner-centered approach. By creating a collaborative environment, it provides a rich resource of learning opportunity for learners and allows learners and teachers to search and study about variety of issues. The aim of this study is to evaluate the impact of educational software designed about fundamental of nursing skills on nursing students' learning of practical skills. Methods: In this semi-experimental study, 164 nursing students of the first semester were recruited through simple random sampling, they were allocated into intervention and control groups (82 people in each group).First, both groups were trained in the traditional way and their practical skills were examined by means of appropriate check lists. Next, the educational software was given to students' assigned to intervention groups. In this period, students of control group had time to review and practice their skills as routine .After 1 month practical skills of both groups were re- evaluated. Results: Results showed that educational software designed about fundamental of nursing skills was effective on nursing students' learning of practical skills. Students' scores of practical skills were significantly different in the intervention group compared with the control group (P<0.05). Conclusion: Educational software can be used as an effective teaching strategy to improve nursing students’ practical skills.